A Stiffness-Fault-Tolerant Control Strategy for an Elastically Actuated Powered Knee Orthosis - Velasco-Guillen, Rodrigo J.; Grosu, Víctor; Carmona-Ortiz, Victor A.; Vanderborght, Bram; Lefeber, Dirk; Font-Llagunes, Josep M.; Beckerle, Philipp (Proceedings of the IEEE RAS and EMBS International Conference on Biomedical Robotics and Biomechatronics, 2020)
Elastic actuators can provide safe human-robot interaction and energy efficient mobility. For this purpose they are ideal for wearable robotic applications. However, such actuators are subject to stiffness faults. We present a stiffness-fault-tolerant control strategy for complex elastic actuators, capable of adapting to changes in output stiffness, and demonstrate it on a smart variable stiffness actuator based on the MACCEPA concept. We develop the dynamics of the actuator and a model-based impedance control scheme. Biomechanical data extracted from the flexion/extension of a real knee joint are used as trajectory reference for the evaluation of the control concept in simulation. Results show that the controlled actuator is capable of tracking a reference trajectory under fault conditions and interaction disturbance while maintaining physical human-robot characteristics.
CRIS-Team Scopus Importer:2021-09-24

A Stiffness-Fault-Tolerant Control Strategy for a Redundant Elastic Actuator - Velasco Guillen, Rodrigo Jose; Furnemont, Raphael; Verstraten, Tom; Beckerle, Philipp (IEEE/ASME International Conference on Advanced Intelligent Mechatronics, AIM, 2022)
Elastic actuators show advantages in energy efficiency and safety in human-robot interaction. However, such actuators might be subject to faults due to their complexity, particularly in elastic and kinematic elements. We present a stiffness-fault-tolerant control strategy for a redundant actuator with multiple elastic actuation units. The control scheme is capable of detecting and compensating for stiffness changes in individual elastic elements. We develop the dynamics of the actuator and a model-based impedance control scheme. The obtained closed-loop dynamic interaction behavior of the system and its stability is analyzed. Oscillatory trajectory simulations are used to evaluate the control strategy. Results show that the controller is capable of tracking a reference trajectory with desired interaction impedance behavior under fault conditions and interaction disturbances, while exploiting redundancy to perform load compensation.
CRIS-Team Scopus Importer:2022-09-30

Comparing online robot joint space trajectory optimization for task space applications - Kramer, Maximilian; Velasco Guillen, Rodrigo Jose; Beckerle, Philipp; Bertram, Torsten (IEEE/ASME International Conference on Advanced Intelligent Mechatronics, AIM, 2021)
Online trajectory planning allows robotic manipulators to adapt to changing environments and dynamic tasks, which becomes increasingly relevant through human-robot interaction. optimizing motion objectives is a common way of planning but is usually conducted in joint space, whereas many planning objectives are rather defined in task space. Joint Space Planning (JSP) first transforms target poses into joint space and then performs conventional optimization. Implicit Task Space Planning (ITSP) uses a special objective function to directly consider task quantities and is similar to economic model predictive control. Remarkably, comparative studies of both approaches with respect to their performance are scarce. This contribution aims at filling this gap by providing a systematic analysis of both methods using a 6-DoF collaborative robot in practical experiments. Results show that the first method is less sensitive to local minima and profits from active reconfiguration abilities while it generates less straight-lined motions and is not able to account for target manifolds in the task space. The second method can easily consider target manifolds and performs more straight-lined motions while it is more sensitive to local minima and provides active reconfiguration only partially. Although the cost function of the second method is significantly more complex, the computational effort relativizes during planning.
CRIS-Team Scopus Importer:2021-09-24
Keywords: Human-Robot-Collaboration; Online Trajectory optimization; Task Space Motion Planning

Compensating elastic faults in a torque-assisted knee exoskeleton: functional evaluation and user perception study - Velasco Guillen, Rodrigo Jose; Bliek, Adna; Font-Llagunes, Josep M.; Vanderborght, Bram; Beckerle, Philipp (Journal of neuroEngineering and rehabilitation, 2024)
Wearable robots are often powered by elastic actuators, which can mimic the intrinsic compliance observed in human joints, contributing to safe and seamless interaction. However, due to their increased complexity, when compared to direct drives, elastic actuators are susceptible to faults, which pose significant challenges, potentially compromising user experience and safety during interaction. In this article, we developed a fault-tolerant control strategy for torque assistance in a knee exoskeleton and investigated user experience during a walking task while emulating faults. We implemented and evaluated the torque control scheme, based on impedance control, for a mechanically adjustable compliance actuator with nonlinear torque-deflection characteristics. Conducted functional evaluation experiments showed that the control strategy is capable of providing support during gait based on a torque profile. A user study was conducted to evaluate the impact of fault severity and compensation on the perception of support, stiffness, comfort, and trust while walking with the exoskeleton. Results from the user study revealed significant differences in participants’ responses when comparing support and stiffness levels without fault compensation. In contrast, no significant differences were found when faults were compensated, indicating that fault tolerance can be achieved in practice. Meanwhile, comfort and trust measurements do not seem to depend directly on torque support levels, pointing to other influencing factors that could be considered in future research.
Created from Fastlane, Scopus look-up
Keywords: Adaptive control; Elastic actuation; Fault tolerance; Human-robot interaction; Impedance control; Wearable robotics

Experimental Evaluation of a Stiffness-Fault-Tolerant Control Strategy on an Elastic Actuator for Wearable Robotics - Velasco Guillen, Rodrigo Jose; Grosu, Victor; Vanderborght, Bram; Font-Llagunes, Josep M.; Beckerle, Philipp (Proceedings of the IEEE RAS and EMBS International Conference on Biomedical Robotics and Biomechatronics, 2022)
Elastic actuator design is primarily motivated by safety in human-robot interaction and energy efficiency. However, the increased complexity when compared to direct drives, makes the system prone to technical faults in elastic and kinematic elements. On the other hand, Variable Stiffness Actuators (VSA) often introduce non-linear torque-deformation relationships. We propose a stiffness-fault-Tolerant control strategy for elastic actuators with non-linear compliant characteristics, capable of adapting to stiffness changes. The control strategy is demonstrated experimentally in a MACCEPA-based elastic actuator designed to power a knee exoskeleton. We develop the general model-based control scheme based on impedance control and adapt it to the experimental actuation system. Experiential evaluations under oscillatory and sigmoid trajectories are considered to analyze performance. Results demonstrate that the control system is capable of accurately tracking a reference trajectory under stiffness variations and interaction disturbance.
CRIS-Team Scopus Importer:2022-11-25

Exploring the Just Noticeable Interaction Stiffness Differences of an Impedance-Controlled Series Elastic Actuator - Velasco Guillen, Rodrigo Jose; Schofer, Felix; Bliek, Adna; Beckerle, Philipp (Actuators, 2023)
The integration of a passive elastic element in series between a motor and its load is popular in many human–robot interaction scenarios. By virtually imposing elastic behavior on the motor, an impedance control can act as a second stiffness to such an actuator. In this study, we investigated how participants perceived the different stiffness settings in a series elastic actuator by measuring the Just Noticeable Difference (JND) of the real stiffness of the elastic element and the virtual stiffness introduced by impedance control. We conducted a user study during which participants interacted with an impedance-controlled Series Elastic Actuator through a lever. During the user study, we varied the real stiffness of the elastic element and the virtual stiffness. We found that participants seem to perceive both the virtual stiffness and the real stiffness in the same way and in accordance to Weber’s law, which states that the stiffness JND is always equal to a fraction of the initial stiffness. Following these findings, we concluded that the impedance controller can implement an effective virtual stiffness with a behavior comparable to a real torsional spring. Therefore, a system combining real and virtual stiffness can simulate a single combined stiffness for a user interacting with it.
Keywords: just noticeable difference; impedance control; elastic actuation; psychophysics

Stiffness-fault-tolerant control strategy for elastic actuators with interaction impedance adaptation - Velasco Guillen, Rodrigo Jose; Furnemont, Raphael; Verstraten, Tom; Vanderborght, Bram; Font-Llagunes, Josep M.; Beckerle, Philipp (Mechatronics, 2024)